Conceptual Framework Strategies for Image Compression: A Review - Ghosh, Sumanta Lal; Chowdhury, Dilip Roy (International Journal of Computer Sciences and Engineering, 2025)
Image compression plays an important role in digital image processing, it is also very crucial for efficient transmission and storage of images. In image compression, does not only concentrate on reducing size but also concentrate on doing it without losing quality and information of image. This paper summarizes the image compression techniques that may be lossy and lossless and research possibilities.